2016
DOI: 10.1190/int-2016-0026.1
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution seismic geomorphology and stratigraphy of a tunnel valley confined ice-margin fan (Elsterian glaciation, Southern North Sea)

Abstract: The deep Middle Pleistocene subglacial incisions of the Southern North Sea (SNS) are commonly infilled by northward gently dipping clinoforms oriented toward the former ice-sheet core. We have focused on the terminal sector of the largest tunnel valley (TV) of the SNS and offer the first high-resolution reconstruction of the geomorphology and stratigraphy of the infill of the glacial incision, as well as the detailed geomorphology of the incision to better understand the genetic mechanisms of these uncommon bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The continuity of the fresh water environment beyond the ice-margin in a proglacial lake that 520 covered the whole clinoform succession is furthermore suggested by seismic reflection data 521 (Benvenuti and Moscariello, 2016). Although very little sedimentological and mineralogical evidence 522 for a proglacial lake in the central part of the SNS is provided in the literature, this contribution 523 supports the studies of Gibbard (2007) and Gupta et al (2007) who were first to hypothesize the 524 existence of a large proglacial lake at glacial maximum in the area between the SNS and the Benelux 525 countries.…”
Section: And 477mentioning
confidence: 99%
“…The continuity of the fresh water environment beyond the ice-margin in a proglacial lake that 520 covered the whole clinoform succession is furthermore suggested by seismic reflection data 521 (Benvenuti and Moscariello, 2016). Although very little sedimentological and mineralogical evidence 522 for a proglacial lake in the central part of the SNS is provided in the literature, this contribution 523 supports the studies of Gibbard (2007) and Gupta et al (2007) who were first to hypothesize the 524 existence of a large proglacial lake at glacial maximum in the area between the SNS and the Benelux 525 countries.…”
Section: And 477mentioning
confidence: 99%
“…A lithological characterization of the material that provides the infill of a British offshore TV suggested that the offshore TVs must have been filled with reworked material that was locally mobilized by glacial processes (Praeg ; Kristensen et al . ; Benvenuti & Moscariello ). However, based on the inferred position of the north European Elsterian ice sheet, the specific internal architecture of the offshore TV infill successions is in apparent contrast with the expected southward displacement of glacial sediments (Figs ).…”
mentioning
confidence: 99%
“…, ; Passchier et al . ; Benvenuti & Moscariello ). Accordingly, the sediment deposited in TVs must have been sourced either locally from the SNS substrate (subglacially mobilized by meltwater flow erosion and ice‐sheet abrasion) or regionally from Scandinavia and the British Isles (subglacially abraded by the ice sheet at a greater distance), or a mixture of both regions.…”
mentioning
confidence: 99%
See 2 more Smart Citations